Strengthening Hotel Branding and Guest Engagement on Revisit Intention through Brand Loyalty (Study of Menu Variation Pasar BiSCR) - Nata, Jiwangga Hadi; Putri, Zhafira Oktavia (Akademi Komunitas MAPINDO, 2024)
The hospitality industry is faced with increasing competition and higher consumer expectations as time goes by. Bumi Surabaya City Resort as an accommodation and culinary service provide in Surabaya, has a desire to maintain and increase their appeal in the market. This study aims to analyse the effect of hotel branding and guest engagement on revisit intention through brand loyalty at the menu variation of Pasar BiSCR which is a buffet restaurant at Bumi Surabaya City Resort. Bumi Surabaya City Resort provides 123 menu variation items every day, including appetizer, soup, main course,dessert, snack, and beverage. In this study, special emphasis is given to the role of menu variations as an important instrument in achieving these goals. This study uses primary data obtained from distributing questionnaires as many as 122 respondents. The research method used in this research is quantitative method using Smart-PLS for data processing. The results of this study indicate that hotel branding has a positive and significant effect on brand loyalty, but has no significant effevt on revisit intention. Guest engagement has a positive and significant effect on brand loyalty and revisit intention. Brand loyalty has a positive and significant effect on revisit intention. Hotel branding has a positive and significant effect on revisit intention through brand loyalty. Guest engagement has a positive and significant effect on revisit intention through brand loyalty.